Bupivacaine 0,25% versus ropivacaine 0,25% in brachial plexus block in dogs of beagle breed Bupivacaína 0,25% versus ropivacaína 0,25% no bloqueio do plexo braquial em cães da raça beagle - Thiago Ignácio Wakoff (Semina: Ciências Agrárias, 2013)
The brachial plexus block (BPB) is a regional anesthesia technique which enables the attainment of surgical procedures distal scapulohumeral articulation. This study aimed to compare the efficacy of ropivacaine and bupivacaine 0.25% without vasoconstrictor in BPB guided by electrical stimulation in dogs. Thirteen male and female beagle dogs underwent a BPB using bupivacaine and ropivacaine 0.25% (4mg/kg), both alone and in different times. The anesthesic block was performed in the right forelimb and as control group the block proceeded in the left forelimb using a solution of sodium chloride 0.9% in volume corresponding to the drug in the contralateral limb. The block was performed after the localization of the radial nerve with the aid of eletrical stimulation, which was infiltrated half the volume of anesthetic calculated and subsequently the remaining solution was administered on the median nerve. We evaluated sensitive and motor latencies and sensitive and motor block total time by clamping technique. In the present study, a technique for electrical stimulation was effective in 100% of animals. Bupivacaine had lower motor latency period, however, the sensitive latency between the two groups showed no statistically significant differences. In the block total time, bupivacaine obtained time significantly higher. Clinical signs characteristic of Horner’s syndrome were present in 15% of animals treated with bupivacaine. Furthermore, two animals presented signs of cardiotoxicity in bupivacaine group. The use of bupivacaine (4mg/kg) without vasoconstrictor in dogs brachial plexus block provided longer analgesia and motor blockade, however, ropivacaine at the same dose and concentration was found to be free of deleterious effects associated of cardiovascular instability, hemodynamic and respiratory. O bloqueio do plexo braquial (BPB) é uma técnica de anestesia regional que possibilita a realização de procedimentos cirúrgicos distais a articulação escapulo-umeral. O objetivo deste trabalho visou comparar a eficácia da ropivacaína e bupivacaína a 0,25% sem vasoconstrictor no BPB, guiado por eletroestimulação, em cães. Foram submetidos ao BPB, 13 cães, machos e fêmeas, da raça beagle, utilizando-se bupivacaína ou ropivacaína a 0,25% (4mg/kg), ambos isolados e em períodos distintos. No membro torácico direito foi realizado o bloqueio anestésico e como grupo controle o bloqueio procedeu-se no membro torácico esquerdo com solução de cloreto de sódio 0,9% no volume correspondente ao do fármaco no membro contralateral. O bloqueio consistiu na localização do nervo radial com o eletroestimulador, onde foi infiltrada a metade do volume anestésico calculado e posteriormente o restante da solução foi administrado sobre o nervo mediano. Foram avaliados os tempos de latência sensitiva e motora e tempos totais de bloqueio motor e sensitivo através da técnica de pinçamentos. No presente estudo, a técnica de eletroestimulação nervosa foi eficaz em 100% dos animais. A bupivacaína apresentou menor período de latência motora, entretanto, os tempos de latência sensitiva entre os dois fármacos não apresentaram diferenças estatísticas significativas. O tempos de bloqueio com a bupivacaína foi significativamente maior Sinais clínicos característicos de Síndrome de Horner estiveram presentes em 15% dos animais tratados com bupivacaína. Ademais, dois animais manifestaram sinais de cardiotoxicidade no grupo bupivacaína. O uso da bupivacaína a 0,25% sem vasoconstrictor na dose de 4mg/kg no bloqueio de plexo braquial em cães conferiu maior tempo de analgesia e bloqueio motor, porém, a ropivacaína na mesma dose e concentração mostrou-se livre de efeitos deletérios associados a instabilidade cardiovascular, hemodinâmica e respiratória.